ICT Education at the Higher Level: Prospects and Opportunities in Geography Education - Adhikari, Sapana; Shrestha, Suman Kumar (Interdisciplinary Research in Education, 2025)
Information and Communication Technology (ICT) has great potential for changing teaching and learning practices, and specifically in geography, which is a subject with a strong reliance upon spatial information, maps, and human and environment analysis. The research methodology was a descriptive and qualitative approach, which made use of minutes of meetings, reports, and secondary sources to analyze the applications of ICT, specifically GIS, remote sensing, virtual simulation, and cartography, in facilitating and enhancing learning, virtual field work, and the establishment of spatial skills and competency. The application of ICT tools has been formulated on the basis of the ICT for Education Master Plan and the Digital Nepal Framework, though it has been hampered by the lack of infrastructure, lack of digital literacy, lack of staff with the right skill sets among the teaching staff, and lack of resources, particularly in the remote areas. The COVID-19 pandemic has greatly accelerated the adoption of distance learning; although it has also brought into focus the disparities and readiness of the institutions. The younger generation, however, has realized the significance of ICT applications in the future work context and is trying very hard to acquire them.